2019
DOI: 10.2478/picbe-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Factors that Determine the Success of ERP Implementation

Abstract: The world boundaries are broken with the advancement of technology and the emergence of digitized industries where economies are connected via the cloud. As a result, effective management of information internally and externally is needed to cope with the quick changes in markets. For a long time, Enterprise Resource Planning (ERP) systems have been used to streamline company processes data, and hierarchy. ERP’s are capable of managing big data, integrating business processes and providing effective communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It considers the existence of an Independent Board of Commissioners and the relationship between independent and dependent variables. An enterprise resource planning system is software that integrates various company activities to increase the flow of information (Gërvalla & Ternai, 2019;Hajj & Serhan, 2019). ERP system implementation is measured using dummy variables (Krismiaji & Aryani, 2014;Weshah et al, 2021).…”
Section: Variables and Measurementsmentioning
confidence: 99%
“…It considers the existence of an Independent Board of Commissioners and the relationship between independent and dependent variables. An enterprise resource planning system is software that integrates various company activities to increase the flow of information (Gërvalla & Ternai, 2019;Hajj & Serhan, 2019). ERP system implementation is measured using dummy variables (Krismiaji & Aryani, 2014;Weshah et al, 2021).…”
Section: Variables and Measurementsmentioning
confidence: 99%
“…2) Train the internal team on the operation and ERP systems functionalities: Several studies have investigated the Critical Success Factors (CSF) of the ERP implementation project [3] [4] [5] [6]. Given the number of failures that have occurred over the years, Muscatello et al reported that 40% of the implementation projects are partially successful while 20% fail [44].…”
Section: A Pre-fit-gap Analysis Recommendationsmentioning
confidence: 99%
“…Scientific research has focused on ERP implementation since it is a significant phase in its life cycle. Researchers have also emphasised some key success factors, given the high degree of failure rate cited in previous research and observed in the field [3] [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%